The relation between d-galactose injection and mitochondrial DNA 4834 bp deletion mutation - Kong, Wei-jia; Wang, Ying; Wang, Qiong; Hu, Yu-juan; Han, Yue-chen; liu, Jun (Experimental gerontology, 2006)
Since, d-galactose ( d-gal) overload model has been used as a premature aging model, we hypothesized that it may also lead to accelerated aging in the inner ear. Furthermore, though the mitochondrial DNA (mtDNA) 4834 bp deletion mutation has been considered as the marker of aging, there is no information available in the literature concerning the mtDNA 4834 bp deletion mutation condition of the d-gal induced premature aging model. We investigate the changes in inner ear enzymatic activity, the occurring of mtDNA 4834 bp deletion in inner ear and other tissues and the relating hearing thresholds after the administration of high dosage (150 mg/kg per day) and low dosage (50 mg/kg per day) of d-gal to rats. Furthermore, the incidence of the mtDNA 4834 bp deletion in different tissues as well as in blood sample was compared. The results showed that daily subcutaneous injections of d-gal into rats for 8 weeks could lead to the biochemical defects and mtDNA 4834 bp deletion in the inner ear tissue and other tissues, which represent the typical aging animals, but the relating hearing threshold shifts (TS) were nearly identical in the three groups. This study also indicates that using of blood samples to detect mtDNA 4834 bp deletion in clinical research might lead to a ‘false negative’ result. A higher sensitive result could be gained using tissue biopsy to examine mtDNA 4834 bp deletion.